Online Handwritten Gurmukhi Character Recognition using Hybrid Feature Set - Singh, Mandeep; Verma, Karun; Gill, Bob; Kaur, Ramandeep (International Journal of Engineering and Technology, 2018)
Online handwriting character recognition is gaining attention from the researchers across the world because with the advent of touch based devices, a more natural way of communication is being explored. Stroke based online recognition system is proposed in this paper for a very complex Gurmukhi script. In this effort, recognition for 35 basic characters of Gurmukhi script has been implemented on the dataset of 2019 Gurmukhi samples. For this purpose, 32 stroke classes have been considered. Three types of features have been extracted. Hybrid of these features has been proposed in this paper to train the classification models. For stroke classification, three different classifiers namely, KNN, MLP and SVM are used and compared to evaluate the effectiveness of these models. A very promising â€œstroke recognition rateâ€ of 94% by KNN, 95.04% by MLP and 95.04% by SVM has been obtained.Â Â